Relation between exposure time on recalcifying fluid and histopathological change of artificial caries - Itoh, Tadashi (Japanese Journal of Oral Biology, 1981)
The recalcifying process of artificial caries by exposure to a calcifying fluidwas studied. The purpose was to clarify the reversible ranges of “recalcification” of enamel surface lesions, whichhad been decalcified at various times. Artificial caries was created by the acidified gelatin-gel method (Silverstone '66) at various intervals (3, 7, 14, 21 and 28 days). After the formation of lesions, thehalf surfaces of the lesions were varnished to serve as controls. They were exposed to a calcifyingfluid in accordance with the formula of Koulourides ('61) for 10 days. Histological and ultrastructuralchanges were examined by contact microradiogram, polarized microscope and scanning electron microscope. Differences in surfaces hues of each samples were read by Chromascan. The samples immersedin acidified gelatin-gel solution for 3, 7 and 14 days showed that decalcification occurred proportionatelyto the experimental periods within a depth of 60-70μ. Whereas, in the samples of 21and 28 days decalcification, the lesions progressed rapidly. Especially, 28 days decalcified lesion reachedabout 200μ. By exposure to the calcifying fluid, the lesions with a depth of about 100μ were apparentlymodified (maximum depth of approximately 30%). However, in more deeper lesions, theeffect of the calcifying fluid was extremely decreased. Amorphous mineral deposits were noticed onthe recalcified surface by scanning electron microscopy, suggesting that this structure may have seriousinfluence on the recalcification phenomenon. Results of the measuring with Chromascan supportedthe above histological changes.